Evaluation of circulating microRNA expression in patients with trigeminal neuralgia: An observational study. Issue 48 (25th November 2020) - Li, Xihan; Wang, Dongxu; Zhou, Jianbin; Yan, Yanfeng; Chen, Leiyao
Abstract : Abstract: Trigeminal neuralgia (TN) is a chronic neuropathic pain that seriously affects the daily life of patients. There is increasing evidence that microRNAs (miRNAs) play an important role in the development of neuropathic pain. In this study, the TaqMan Low Density Array (TLDA) was used to analyze the serum miRNA levels of 28 TN patients, and 31 healthy people without any neuropathic pain were used as controls. The results showed that the expression profile of serum miRNA in TN patients was different from that in healthy controls. Compared with the control group, 13 miRNAs in the serum of TN patients were up-regulated and 115 miRNAs were down-regulated by >2 times. Quantitative reverse transcription PCR (RT-qPCR) analysis and receiver operating characteristic (ROC) curve were performed. The analysis further confirmed that the expression levels of 4 miRNAs, including miR-132-3p, miR-146b-5p, miR-155-5p, and miR-384, were significantly higher than those of healthy controls, and the difference was statistically significant. This study preliminarily confirmed the changes of serum miRNA expression profile in TN patients. Among them, 4 kinds of serum miRNA are likely to be related to the occurrence and development of TN.